Brain Sensory Organs of the Ascidian Ciona robusta: Structure, Function and Developmental Mechanisms - Olivo, Paola; Palladino, Antonio; Ristoratore, Filomena; Spagnuolo, Antonietta (Frontiers in Cell and Developmental Biology, 2021)
During evolution, new characters are designed by modifying pre-existing structures already present in ancient organisms. In this perspective, the Central Nervous System (CNS) of ascidian larva offers a good opportunity to analyze a complex phenomenon with a simplified approach. As sister group of vertebrates, ascidian tadpole larva exhibits a dorsal CNS, made up of only about 330 cells distributed into the anterior sensory brain vesicle (BV), connected to the motor ganglion (MG) and a caudal nerve cord (CNC) in the tail. Low number of cells does not mean, however, low complexity. The larval brain contains 177 neurons, for which a documented synaptic connectome is now available, and two pigmented organs, the otolith and the ocellus, controlling larval swimming behavior. The otolith is involved in gravity perception and the ocellus in light perception. Here, we specifically review the studies focused on the development of the building blocks of ascidians pigmented sensory organs, namely pigment cells and photoreceptor cells. We focus on what it is known, up to now, on the molecular bases of specification and differentiation of both lineages, on the function of these organs after larval hatching during pre-settlement period, and on the most cutting-edge technologies, like single cell RNAseq and genome editing CRISPR/CAS9, that, adapted and applied to Ciona embryos, are increasingly enhancing the tractability of Ciona for developmental studies, including pigmented organs formation.